2016
DOI: 10.1155/2016/5296536
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Presentation of Vaginal Cuff Dehiscence after Robotic Hysterectomy for Gynecologic Cancer: A Case Series and Review of the Literature

Abstract: Background. Vaginal cuff dehiscence after hysterectomy has varying incidence according to surgical approach, with highest rates associated with laparoscopic surgery. Comparative data on timing of diagnosis describe a wide range of clinical presentation from weeks to years after hysterectomy. Limited reports have focused specifically on delayed presentation of vaginal cuff dehiscence. Cases. All cases of vaginal cuff dehiscence at our institution between 2005 and 2015 were collectively reviewed and three cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This is corroborated by studies that demonstrate a lower rate of surgical complications according to the surgical technique used and previous training. 23,24 It is also important to stress that the data herein demonstrated reflects specifically the studied population in a specific condition of knowledge and training. Although we personally agree that the bimanual knot tying technique seems safer and may be faster, it could be true that with a longer training or larger sample size this concept would change.…”
Section: Discussionmentioning
confidence: 79%
“…This is corroborated by studies that demonstrate a lower rate of surgical complications according to the surgical technique used and previous training. 23,24 It is also important to stress that the data herein demonstrated reflects specifically the studied population in a specific condition of knowledge and training. Although we personally agree that the bimanual knot tying technique seems safer and may be faster, it could be true that with a longer training or larger sample size this concept would change.…”
Section: Discussionmentioning
confidence: 79%
“…A recent in vitro study evaluating the effect of electrode size on the depth of coagulation showed that use of a sharp point electrode is associated with more superficial coagulation [7] . As in our clinic, electrocautery is commonly used for colpotomy during laparoscopic hysterectomy, which may lead to poor blood supply to the wound [8] . The cutting mode has been thought to cause less harm than the coagulation mode; however, both can be used during colpotomy if more bleeding than expected occurs.…”
Section: Discussionmentioning
confidence: 99%
“…For both patients, dehiscence occurred following minimally invasive hysterectomies (robotic-assisted laparoscopic in the Peyser case and laparoscopic in our case). Additionally, both women underwent hysterectomy for malignant indications, that can predispose to wound healing complications [2]. In contrast, the patient described in the Peyser case was 25 years old and obese while our patient was 35 years old with a BMI of 20.5.…”
Section: Discussionmentioning
confidence: 60%
“…VCD with evisceration occurs in the majority of reported cases with an estimated incidence of 0.032 to 1.2% [1]. VCD can present with a range of symptoms including abdominal and pelvic pain or pressure, leaking of vaginal fluid, vaginal bleeding, or sometimes no symptoms with identification on clinical examination [2]. Identification of VCD requires immediate surgical management to prevent additional complications including bowel prolapse/ necrosis and sepsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation